KAJIAN PEMBENTUKAN OTORITAS JASA KEUANGAN DI INDONESIA: MELIHAT DARI PENGALAMAN DI NEGARA LAIN - AMINA, ZAIDATUL (Jurnal Akuntansi AKUNESA, 2012)
Experience of the crisis in Indonesia in 1997-1998, followed by BLBI embezzlement and Century Bank case in 2008, is due to the failure of Bank Indonesia as the supervisor of banks in Indonesia, prompting the government to establish an independent supervision system of financial institutions, namely Otoritas Jasa Keuangan (OJK). This study aims to describe and compare the application of independent supervision systems in Europe and Asia countries such as Britain, Germany, Japan and Korea, resulting in an overview of the application of independent supervision of financial institutions (OJK) which may be appropriate in Indonesia. Research methodology used in this paper is a comparative descriptive method with domain and taxonomic analysis, while the data collection techniques using literature studies. The results of this study is the OJK surveillance system in Indonesia should be supported by implementation of Good Corporate Governance, and good coordination between OJK, central banks and other financial institutions and the independence of the functions, duties and authority are carried out by OJK should be clear and not influenced by government and the power of other financial institutions. Key words: financial supervision, independent supervision and OJK